Collecting duct-specific knockout of sphingosine-1-phosphate receptor 1 aggravates DOCA-salt hypertension in mice. Issue 8 (August 2021) - Hu, Gaizun; Zhu, Qing; Wang, Weili; Xie, Dengpiao; Chen, Chaoling; Li, Pin-Lan; Ritter, Joseph K.; Li, Ningjun
Abstract : Objective: We have previously reported that renal medullary sphingosine-1-phosphate (S1P) regulates sodium excretion via the S1P type-1 receptor (S1PR1). As S1PR1 is predominantly expressed in collecting ducts (CD), the present study tested the hypothesis that the CD-S1PR1 pathway plays a critical role in sodium excretion and contributes to salt-sensitive hypertension. Methods: CD-specific S1PR1 knockout mice were generated by crossing aquaporin-2-Cre mice with S1PR1-floxed mice. Renal sodium excretion and arterial pressure were compared between wild type and KO mice in response to high-salt challenges and treatment of deoxycorticosterone acetate (DOCA) salt. Results: Protein levels of renal medullary S1PR1 were increased by 100% after high-salt intake, whereas DOCA treatment with high-salt intake blocked the increase of S1PR1 levels. Urinary sodium excretions in knockout mice were decreased by 60% compared with wild type mice after acute intravenous sodium loading (0.84 ± 0.16 vs. 2.22 ± 0.62 μmole/min per g kwt). The pressure natriuresis was impaired in knockout mice compared with wild type mice (4.32 ± 1.04 vs. 8.73 ± 0.19 μmole/min per g kwt). The chronic high-salt intake-induced positive sodium balance was enhanced in knockout mice compared with wild type mice (5.27 ± 0.39 vs. 2.38 ± 1.04 mmol/100 g BW per 24 h). After 10-day DOCA-salt treatment, knockout mice developed more severe hypertension than wild type mice (SBP 142 ± 8 vs. 115 ± 4 mmHg). Conclusion: The deletion of CD-S1PR1 reduced sodium excretion, promoted sodium retention, and accelerated DOCA-salt-induced salt-sensitive hypertension, suggesting that the CD-S1PR1 signaling is an important antihypertensive pathway by promoting sodium excretion and that impairment of renal medullary S1PR1 may represent a novel mechanism for salt-sensitive hypertension.